Implementation and Visualization of Business Intelligence Based Budget in Ngawi District Financial Agency 2021-2023 - Pudyaningrat, Elsa; Nugrahaningsih, Putri (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2024)
This research aims to determine the s of budget implementation and visualization from 2021 to 2023 in the Financial Agency of Ngawi Regency which uses Business Intelligence Power BI as a basis for decision-making. This is quantitative research which used a descriptive-quantitative approach method. To collect the data, the researchers used a literature study and documentation of the summary of APBD (Anggaran Pendapatan Belanja Daerah/APBD) data in the Financial Agency of Ngawi Regency from 2021 to 2023. The results indicate that there are fluctuations in the Regional Income, Regional Expenditures, and Regional Financing when implementing and visualizing budget data (APBD) using Business Intelligence Power BI. Cumulatively, the total APBD is Rp 13,732,224,315,602.00, with a total growth of 210.3%. The next result is the Financial Agency of Ngawi Regency can use Business Intelligence Power BI to analyse and visualize the APBD budget data for decision-making purposes. It shows that this system can be used for decision-making by this agency because it is user-friendly, fast, accurate, and informative.